KAJIAN GEOLOGI TEKNIK PADA RENCANA PEMBUATAN TUNNEL TAMBANG BAWAH TANAH (Jurnal Geologi Pertambangan (JGP), 2015)
Geological engineering study aimed at knowing the Physical and MechanicalProperties of the rock.In the implementation of research activities in the fieldhave been conducted Taking a sample which is then tested in the laboratory,which is selected based on the representation of the drill hole. Tests performedincluded moisture content test, test the specific gravity, Comprasion Unixial test,shear strength test, Pull strength test. Laboratory testing of samples taken fromthe Geotek 3 drill holes carried out in the Laboratory of Geomechanics andmining equipment Faculty of Mining and Petroleum Engineering ITB Bandung.Be Based results hereafter devised Design Study Geotechnical Hole Aperture Asthe main entrance (main roadway) with Dimensions (width 5 m; height 2.5 m) byusing software Phase2. Dimensional aperture hole is adjusted to thespecifications of the tool unit (road header). Dimensions of openings are made asefficient as possible, the larger dimensions of openings, the greater thedeformation of rocks that occur and the smaller the safety factor The wholedimensional aperture hole 4 Level include Level 1, Level 2, Level 3, Level 4, eachlevel is 30m by using rigid steel arch support. Estimates of rock debris at theopenings will be calculated to determine the model and the value of FK openings.Keywords : Geomekanika,main roadway,rigid steel arch,Tunnel.